Magnetic structures and optical properties of rare-earth orthoferrites RFeO3 (R = Ho, Er, Tm and Lu). (February 2019) - Wang, Zhao-Qi; Lan, Yang-Shun; Zeng, Zhao-Yi; Chen, Xiang-Rong; Chen, Qi-Feng
Abstract: Rare-earth orthoferrites have received great interest due to their exotic optical and ferroelectric features. In this work, a comprehensive research on the magnetic and optical properties of four rare-earth orthoferrites RFeO3 (R = Ho, Er, Tm and Lu) is performed through first-principle calculations. We find that the magnetic states of orthorhombic phase are sensitive to the ionic spin ordering and ground state properties, which could be clearly observed from the electronic structure and magnetic characters. We further discuss the intrinsic relationship among ground state arrangements, magnetic anisotropy, and magnetic order transitions. It is shown that the spin reorientation transition takes place in the ac plane, but far from the bc plane. According to the dielectric function spectra in the range of 0–5.5 eV, the values of optical band gap are found to be close to 2.60 eV. Moreover, the optical absorption band exhibits a blue-shift during the transition from hexagonal to orthorhombic phase. These results can be used to evaluate the magnetic and optical properties for the whole lanthanide ferrites. Highlights: The cooperative coupling between the octahedral rotation and Jahn-Teller effect is responsible for the magnetic anisotropy and the stability of system. The anisotropic magnetic energy proves for the first time that the spin-reorientation transition takes place in the ac plane, but far from the bc plane. The values of optical band gap are close to 2.60 eV and the optical absorption band exhibits a blue-shift during the transition from the hexagonal to orthorhombic phase.